2017
DOI: 10.1002/poc.3713
|View full text |Cite
|
Sign up to set email alerts
|

DFT study on abstraction reaction mechanism of oh radical with 2-methoxyphenol

Abstract: Reaction mechanism of 2-methoxyphenol (2MP) (guaiacol) with OH radical has been performed using density functional theory methods BH&HLYP and MPW1K method with 6-311++G(d,p) basis set. Single-point energy calculations were done using CCSD(T)/6-311++G(d,p). The theoretical results reveal that the hydrogen abstraction from methoxy group is found to be the dominant reaction channel with an energy barrier of 9.31 kcal/mol. Also, time-dependent density functional theory calculations have been performed using BH&HLY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 74 publications
0
14
0
Order By: Relevance
“…In addition, differences between density functional theory (DFT) calculations and lab studies have been also observed. For example, the DFT-predicted rate constant of 2-methoxyphenol with OH radicals (12.19 × 10 −11 cm 3 molecule −1 s −1 ) is higher than that (7.53 × 10 −11 cm 3 molecule −1 s −1 ) obtained by a lab study (Coeur-Tourneur et al, 2010a;Priya and Lakshmipathi, 2017). This suggests that it is necessary to determine the rate constants of multifunctional organics through lab experiments.…”
Section: Rate Constantmentioning
confidence: 79%
See 1 more Smart Citation
“…In addition, differences between density functional theory (DFT) calculations and lab studies have been also observed. For example, the DFT-predicted rate constant of 2-methoxyphenol with OH radicals (12.19 × 10 −11 cm 3 molecule −1 s −1 ) is higher than that (7.53 × 10 −11 cm 3 molecule −1 s −1 ) obtained by a lab study (Coeur-Tourneur et al, 2010a;Priya and Lakshmipathi, 2017). This suggests that it is necessary to determine the rate constants of multifunctional organics through lab experiments.…”
Section: Rate Constantmentioning
confidence: 79%
“…It is well known that a high NO x concentration almost always plays a negative role in NPF and SOA formation be-cause the reaction of NO with RO 2 radicals would result in the formation of more volatile products compared to the reaction of HO 2 with RO 2 radicals (Sarrafzadeh et al, 2016). Previous studies reported that nitro-substituted products were the main products for SOA formed from OH-initiated reactions of phenol precursors, including methoxyphenols, in the presence of NO x (Ahmad et al, 2017;Finewax et al, 2018;Lauraguais et al, 2012Lauraguais et al, , 2014b.…”
Section: Effect Of No 2 On Soa Formationmentioning
confidence: 99%
“…22,30 Then hydroxyl radicals attack hydrogen atoms in the α-methylene (CH 2 ) and also hydroxyl groups (OH) of dextran. 22 These reactive sites can be linked to the methoxy group of the curcumin molecule 31 (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…In Scheme 2 (pH 4, IPA or NaBC, under air-saturated conditions), additional radicals generated ( • HO2 and CO3 (Priya and Lakshmipathi, 2017;Sun et al, 2019), generating a hydroperoxide (-OCH2OOH) that readily decompose to form -OCH2O • and • OH (Yaremenko et al, 2016). -OCH2O • is finally transformed into -OCHO with the elimination of HO2 in the presence of O2 (Sun et al, 2019).…”
Section: Photo-oxidation Pathways Of Vanillin Via Direct Photosensitization and In The Presence Of Nitratementioning
confidence: 99%